Acceptance of High Protein Nuggets as an Animal Side Dish for Toddlers Wasting - Winda Veronica; Afriyana Siregar; Podojoyo Podojoyo (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background. One of the nutritional statuses of children is wasting. Wasting is a group of undernourished, directly caused by inadequate nutrition and infectious diseases. One kind of food product that can be a high-protein animal side dish as a nutritional value enhancer for children with waste is High Protein Nuggets. High Protein Nuggets are nuggets made from the main ingredient of catfish. Research Methods. This study used experimental research with a complete random design (RAL) non-factorial. In this study, the best formulation was found, namely the formula F3, which included 175g catfish meat, 25g carrots, 80g eggs, 40g wheat flour, 40g bread flour, 15g leeks, 20g coconut milk, and 2g pepper. Research Result. From the effects of analysis of comparable levels, content in the best of high protein nuggets formulation 100 grams contains energy 325,6 kcal, protein 12,75 grams, fat 22,12 grams, and carbohydrates 18,63 grams.  Conclusion. Based on organoleptic data, the chosen formula is F3 Nugget, high in protein, with F3 having the most significant average value of each parameter assessment (taste, color, aroma, and texture).